Endothelial dysfunction promotes the transition from compensatory renal hypertrophy to kidney injury after unilateral nephrectomy in mice. - Nagasu, H; Satoh, M; Kidokoro, K; Nishi, Y; Channon, K; Sasaki, T; Kashihara, N (2012)
Loss of functional nephrons associated with chronic kidney disease induces glomerular hyperfiltration and compensatory renal hypertrophy. We hypothesized that the endothelial nitric oxide synthase (eNOS) [soluble guanylate cyclase (sGC)] protein kinase G (PKG) pathway plays an important role in compensatory renal hypertrophy after unilateral nephrectomy. Analysis of mice subjected to unilateral nephrectomy showed increases in kidney weight-to-body weight and total protein-to-DNA ratios in wild-type but not eNOS knockout (eNOSKO) mice. Serum creatinine and blood urea nitrogen increased after nephrectomy in eNOSKO but not in wild-type mice. Furthermore, Bay 41-2272, an sGC stimulator, induced compensatory renal hypertrophy in eNOSKO mice and rescued renal function. The NO donor S-nitrosoglutathione (GSNO) and Bay 41-2272 stimulated PKG activity and induced phosphorylation of Akt protein in human proximal tubular cells. GSNO also induced phosphorylation of eukaryotic initiation factor 4E-binding protein and ribosomal protein S6. Our results highlight the importance of the eNOS-NO-PKG pathway in compensatory renal hypertrophy and suggest that reduced eNOS-NO bioavailability due to endothelial dysfunction is the underlying mechanism of failure of compensatory hypertrophy and acceleration of progressive renal dysfunction.